Analysis of fracture processes in reinforced concrete beams without stirrups (Fracture and Structural Integrity, 2021)
The analysis of fracture processes which led to shear failure in reinforced concrete beams without transverse reinforcement was performed on the basis of test results from the author’s own experimental investigation and numerical simulations. The variable parameters during the experiment were a beam’s length and a shear span. It was observed that the character of failure in the beams depended on the beam’s length and the span-to-depth ratio. In slender beams characterized by the shear span-to-depth ratio 3.4 and 4.1, the formation of the critical diagonal crack caused a brittle, sudden failure and the shear capacity was low. In short beams, when the shear span-to-depth ratio was 1.8 and 2.3, the failure process had a more stable character with a slow developing of inclined cracks and the significantly higher load capacity was reached. The activation of various shear transfer mechanisms was examined with regard to the slenderness of the member and the transition between a beam action which took place in slender beams to an arch action which predominated in short beams was described.
Keywords: Fracture process; Reinforced concrete; Shear failure